598-P: Sex-Specific Differences of Human Skeletal Muscle—A Multiomics Exercise Study - DREHER, SIMON I.; GOJ, THOMAS; VON TOERNE, CHRISTINE; HOENE, MIRIAM; IRMLER, MARTIN; OUNI, MERIEM; JÄHNERT, MARKUS; BECKERS, JOHANNES; PETER, ANDREAS; BIRKENFELD, ANDREAS L.; SCHÜRMANN, ANNETTE; HAUCK, STEFANIE M.; et al. (Diabetes (New York, N.Y.), 2024)
Exercise is a potent skeletal muscle stimulus and one of the most effective strategies to prevent muscle loss and type 2 diabetes. Biological sex-based differences are reported for aerobic capacity, muscle mass, and exercise performance. We aimed to provide a yet missing comprehensive picture of molecular differences between female and male skeletal muscle at baseline, after acute exercise and training. Further we investigated which differences were conserved in vitro. We characterized muscle biopsies from 25 (16f/9m) subjects in a multi-omics approach employing epigenomics, transcriptomics and proteomics at baseline, after acute exercise and 8 weeks of supervised endurance training. Donor matched myoblasts and myotubes were analyzed in vitro. We found differential CpG-site methylation in 16.012 genes, 1.366 differentially expressed genes and 120 proteins at baseline. Differential transcripts were associated with translational regulation, histone methylation, glucose homeostasis and insulin signaling. Type-2 fast-twitch fiber-type proteins were elevated in males, along with proteins regulating glycolysis. Y-linked transcript expression was conserved in vitro, but only a few differences in expression of autosomal genes, e.g. elevated LDHB in females. Acute exercise upregulated oxidative stress-responsive transcripts predominantly in males. After 8-week-training, both sexes had upregulated mitochondrial proteins involved in substrate oxidation and ATP production, while glycolytic fiber marker MYH1 and MYH3 were only reduced in males. Thus, sex specific differences exist in resting skeletal muscle and in exercise adaptation on epigenomic, transcriptomic and proteomic level. The few conserved differences in vitro hint towards hormonal or yet undefined mechanisms. Training might mitigate initially differential responses to exercise. The question remains whether there are sex specific differences within individual fiber-types or whether it is just a matter of composition.